2010
DOI: 10.3928/01477447-20100722-42
|View full text |Cite
|
Sign up to set email alerts
|

Periprosthetic Joint Infection: Treatment Options

Abstract: Periprosthetic joint infection has become the most common cause of failure following total knee arthroplasty. Over the past 4 decades, treatment of this disease has evolved with technological innovations and pathogen profiling. The appropriate treatment selection is dependent on patient immune system quality, timing of symptom onset, and pathogen type. Antibiotic suppression alone is reserved for those cases without drainage, low-virulent antimicrobial-susceptible pathogens, and patients whose level of health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
83
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(95 citation statements)
references
References 12 publications
2
83
0
6
Order By: Relevance
“…These include a combination of medical (antibiotic therapy) and surgical treatments [12]. Regarding the antibiotic therapy, intravenous ampicillin, gentamicin, or vancomycin is sufficient for non-VRE species [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include a combination of medical (antibiotic therapy) and surgical treatments [12]. Regarding the antibiotic therapy, intravenous ampicillin, gentamicin, or vancomycin is sufficient for non-VRE species [8].…”
Section: Discussionmentioning
confidence: 99%
“…Irrigation and débri-dement, one-stage exchange arthroplasty, two-stage exchange arthroplasty, and salvage surgeries (fusion and amputation) are available surgical options for management of PJI. Among these options, two-stage exchange arthroplasty is the preferred method of treatment of patients with chronic PJI in North America [12]. The exact success rate of these interventions is not well known and varies widely depending on what is considered a success.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors believe débride-ment should be performed only in the early stage of infection [22]. When the infection is chronic, Parvizi et al [18] considered prosthesis removal mandatory. Reimplantation of a new TKA is generally performed in a subsequent stage after a variable period of time (two-stage protocol) and initial control of the infection [24].…”
Section: Introductionmentioning
confidence: 99%
“…However, there might be a higher risk of persistence or recurrence of the index infection due to a deficient débridement or insufficient antibiotic treatment. Some authors consider two-stage protocols for control of infections in total joint arthroplasty the gold standard [10,18]. Kalore et al [11] suggested one-stage protocols were contraindicated or should be reserved for selected patients (no fistula, no severe bone damage, known pathogen with high sensitivity to antibiotics, etc).…”
Section: Introductionmentioning
confidence: 99%
“…In the presented case, Sphingomonas paucimobilis was grown in the culture of the tissue biopsy sample obtained from the sinus tract. In the literature review, it was determined that S. paucimobilis infection had always been defined as accompanying different comorbidities, such as malignancy, diabetes mellitus, alcoholism, hepatic cirrhosis, late stage renal failure, chronic obstructive pulmonary disease, burn wounds, and acquired immune deficiency syndrome (10). In the presented case, the comorbidity was tibial proximal osteosarcoma, in addition to secondary immune suppression due to the previous chemotherapy.…”
Section: Tartışma Ve Sonuçmentioning
confidence: 94%